Vegetation analysis and environmental indicators of an arid tropical forest ecosystem of Pakistan. (September 2022) - Majeed, Muhammad; Khan, Arshad Mahmood; Habib, Tariq; Anwar, Muhammad Mushahid; Sahito, Hakim Ali; Khan, Nasrullah; Ali, Kishwar
Graphical abstract: Highlights: Interactions between vegetation and environment of the district Jhelum, Pakistan were analyzed. A total of five significantly different plant associations were observed. Distance to river was the leading predictor of vegetation compositional variations. Distance to river as proxy of ground water table depth is more important than rainfall. Soil pollution and anthropogenic disturbances are disrupting normal ecosystem functioning. Abstract: Vegetation composition and/or plant species co-existence is influenced by the environmental variations in any region. The ecological knowledge and order of importance of selected environmental variations is important in conservation and management of plant resources. Based on relevant knowledge gap, the study area of district Jhelum, Pakistan lying in an arid-tropical zone was selected to explore the vegetation types and their driving environmental factors by using latest multivariate statistical approaches. For this, the entire district was ecologically explored to collect the natural wild vegetation and environmental data from January 2018 to December 2020. The study area was partitioned into 171 grids (5 × 5 km 2 ). In each grid, three sites were randomly selected (i.e. 513 samples), and subsequently-nine plots were laid at each sampling site (i.e. 1539 plots). Different statistical tests including Monte Carlo permutation test, Indicator Species Analysis (ISA), hierarchical classification, ordination, and variation partitioning were applied to seek the potential number of vegetation types, plant species composition, classification of the studied samples, order of importance of the considered predictors and groups of environmental variables respectively. The findings of this study indicated that all the documented 291 plant species belong to five statistically significant (p < 0.05) plant communities. Out of thirty (30) considered environmental variables, canonical correspondence analysis suggested the significant role of distance from the river, altitude, latitude, slope, temperature, rainfall, distance from the cropland, grazing and deforestation pressure, and soil pollutants including chromium, arsenic and nickel concentrations. Similarly, plant diversity patterns were found strongly associated with the selected local environmental conditions. This study concluded that distance from the river (a potential leading proxy of ground water table depth) is relatively more important than the rainfall variability in this tropical arid area. Hence, the relative proportion of xerophytic plant species was found higher in the western parts compared to eastern parts adjoining the river Jhelum. Anthropogenic disturbances and potentially toxic metals were found disrupting the normal ecosystem functioning at the local scale in this arid tropical region, and need immediate attention to save the valuable local biodiversity.